A Parametric Design Approach for Affordable Customized 3D Socket for Transradial Upper Limb Prostheses - Saldarriaga, A.M.; Romero, E.; Abarca, V.E.; Elías, D.A. (Institute of Electrical and Electronics Engineers, 2024)
In upper limb prosthetics, customization of prosthetic designs is necessary to adapt them to each user’s unique anatomical dimensions and ensure comfort and functionality. In addition, streamlining the process is essential to reduce the waiting time for people in need. In this context, an approach to parametric and transradial prosthesis design, which emerges as the primary tool to meet these challenges, is presented. In this way, the step-by-step process of how this paradigm is used in conjunction with other design techniques is detailed, thus obtaining a prosthetic stump-forearm interface and a forearm socket fabricated by 3D printing with PLA material. Likewise, customizing these elements guarantees a natural and realistic imitation of a forearm, which leads to the user feeling a sense of belonging toward the prosthesis itself. The results of this study show the fabrication of the final prosthetic design and its respective preliminary evaluation on a volunteer user with a long transradial congenital amputation condition based on the anthropometric measurements described in the design process. In addition, this process can optimize the design time compared to other prosthetic procedures, facilitating their productivity by manufacturing. This process, optimized in design time and computational load, benefits the creation of affordable prosthetic devices and sets a precedent in parametric design research, with potential for future applications in biomedical innovations.
Keywords: Parametric statistics; Computer science; Mathematics; https://purl.org/pe-repo/ocde/ford#1.01.03